2016
DOI: 10.1007/s10393-016-1102-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antimicrobial Peptides in Amphibian Defense Against Trematode Infection

Abstract: Antimicrobial peptides (AMPs) contribute to the immune defenses of many vertebrates, including amphibians. As larvae, amphibians are often exposed to the infectious stages of trematode parasites, many of which must penetrate the host’s skin, potentially interacting with host AMPs. We tested the effects of the natural AMPs repertoires on both the survival of trematode infectious stages as well as their ability to infect larval amphibians. All five trematode species exhibited decreased survival of cercariae in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In experimental exposure trials, LaFonte and Johnson () found that larvae of Hyla versicolor , H. cinerea and H. gratiosa cleared infections within 72 hr, which is 10× faster than in 11 other species of frogs, toads and salamanders (Johnson & Hartson, ; Johnson et al., ). Although the mechanism underlying this resistance is unknown, it was not driven by differences in host antimicrobial peptides (Calhoun et al., ), and immune suppression (via corticosterone) caused only minor increases in infection (LaFonte & Johnson, ). An important priority will thus involve identifying the mechanistic pathways through which these and other skin secretions—including TTX—affect parasite infection success and persistence.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental exposure trials, LaFonte and Johnson () found that larvae of Hyla versicolor , H. cinerea and H. gratiosa cleared infections within 72 hr, which is 10× faster than in 11 other species of frogs, toads and salamanders (Johnson & Hartson, ; Johnson et al., ). Although the mechanism underlying this resistance is unknown, it was not driven by differences in host antimicrobial peptides (Calhoun et al., ), and immune suppression (via corticosterone) caused only minor increases in infection (LaFonte & Johnson, ). An important priority will thus involve identifying the mechanistic pathways through which these and other skin secretions—including TTX—affect parasite infection success and persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides from poisonous animals are described for a number of scorpion peptides, as well as peptides from snakes, frogs, bees ( Apis sp. ), etc., as part of their host defense system [37,38,39,40,41,42,43,44,45,46]. For scorpions in particular, it has been proposed that the presence of antibacterial peptides protects the venom gland from pathogenic infections or potentiates toxin action [47].…”
Section: Discussionmentioning
confidence: 99%
“…The AMPs are substances evolutionarily ancient found in bacteria, fungi, plants and animals. These substances differ in molecular size, spectrum of action; they are considered the major components of the innate immune system and work in defense against infections caused by viruses, bacteria and fungi [20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Furthermore, recent studies indicate that the AMP may exercise activities such as immunological modulators [34,35] in the treatment of cancer [36] , in the recovery of skin lesions and as an alternative in the treatment of biofilms formed by pathogenic microorganisms [37] .…”
Section: General Characteristics Of the Ampsmentioning
confidence: 99%